Evolution of the total ozone field during the breakdown of the Antarctic circumpolar vortex - Bowman, Kenneth P. (1990)
Nine years of total ozone measurements from the TOMS on Nimbus 7 are used to study the evolution of the Southern Hemisphere total ozone field during the breakdown of the Antarctic circumpolar vortex. The TOMS data provide detailed maps of the morphology of the ozone field and reliable estimates of the vertically integrated meridional transport of ozone during the springtime period when the breakdown occurs (September, October, November). In estimating the ozone transport, chemical effects, including those thought to be responsible for the Antarctic ozone hole, are neglected. This approximation appears to be valid for time scales of a few days to a week. On this time scale, local ozone changes are primarily due to transport. Planetary-scale waves, especially zonal wave numbers 1 and 2 dominate the eddy variance and ozone transport. Wave number 1 is quasistationary, while wave number 2 is eastward moving with a period of about 10 days.